Carcinomatous meningitis complicating carcinoma of uterine cervix: an uncommon presentation - Anusha Konakalla VL; Das P; Rukmangdha N (Journal of Clinical and Scientific Research, 2016)
Carcinomatous meningitis is a rare clinical entity associated with gynaecological malignancies. However, it is an unusual occurrence in carcinoma of uterine cervix. Here we report a case of a 55-year-old female who was diagnosed to have carcinoma of uterine cervix stage IIB and was started on radiotherapy to whole pelvis with curative intent. One week later she complained of sudden onset of headache,vomiting and neck rigidity. Contrast enhanced computed tomography (CECT) brain showed diffuse meningeal enhancement of sulci. Cytopathological examiniation of cerebrospinal fluid revealed malignant cells which confirmed the diagnosis of carcinomatous meningitis. She received palliative whole brain radiotherapy and intrathecal methotrexate that resulted in symptomatic improvement during and immediately following treatment. She died four weeks after discharge from the hospital.